Selection of medical students : the relationship between pre-admission academic achievements & students' profiles to performance in medical school - Hod, Rafidah (2006)
AIM: A retrospective study to determine the association between pre-admission academic achievement and students' profiles with their medical school performance was conducted in the Faculty of M~dicine and Health Sciences, Universiti Putra Malaysia from May 2005 to October 2005. This study analysed 5 Sijil Pelajaran Malaysia (SPM) subjects (i.e. Bahasa Malaysia, English, Biology, Chemistry and Physics) and type of pre-admission programme [matriculation or Sijil Tinggi Pelajaran Malaysia (STPM)]. Students' profiles include their demographic variables and motivational factors. METHOD: All students who have gone through the pre-clinical years and all the clinical postings in Year 3 and Year 4 are included in this study (n=147). The outcome measures were the results of Year 2, postings of Medicine-Surgery, Paediatrics, Obstetrics & Gynaecology, Psychiatry, ENT, Dermatology, Ophthalmology. Year 2 examination results represent performance in the pre-clinical years while the rest of the outcomes represent performance in the early clinical years. The outcome of grades A, B+ and B are considered as good results while grades C+, C and F are average/poor results. Statistical tests used to determine the associations are Chi-square and Fisher's Exact test. Further analysis was carried out using logistic regression to examine the relationship between important variables and all the outcomes. RESULTS: Univariate analysis found variables associated with good performance in medical school to include: four SPM subjects (i.e. English, Biology, Chemistry and Physics), STPM programme, male, Chinese and students from day schools. At final assessment, students who were from the STPM programme were 12.2 times more likely to perform well in Year 2, 16.1 times more likely in Medicine-Surgery and 3.6 times more likely in Ophthalmology. Students who were good in Biology were 2.6 times more likely to perform well in Year 2, while those good in Physics were 5 times more likely to perform well in Medicine-Surgery, students who did well in Chemistry were 2.4 times more likely to perform well in Psychiatry, 4.8 times more in ENT and 2.7 times more in Ophthalmology. Those from day school were 3.5 times more likely to do well in Psychiatry. Parental wish was inversely related to the performance in Ophthalmology while choice of wide range of job options in medicine was inversely related to outcomes in Year 2 and ENT. CONCLUSION: This study suggests that there is a relationship between pre-admission qualifications, students' profile and subsequent performance in the medical school.